Mesenchymal stromal cells from bone marrow treated with bovine tendon extract acquire the phenotype of mature tenocytes - Lívia Maria Mendonça Augusto; Diego Pinheiro Aguiar; Danielle Cabral Bonfim; Amanda dos Santos Cavalcanti; Priscila Ladeira Casado; Maria Eugênia Leite Duarte (Revista Brasileira de Ortopedia, 2016)
ABSTRACT OBJECTIVE: This study evaluated in vitro differentiation of mesenchymal stromal cells isolated from bone marrow, in tenocytes after treatment with bovine tendon extract. METHODS: Bovine tendons were used for preparation of the extract and were stored at -80 °C. Mesenchymal stromal cells from the bone marrow of three donors were used for cytotoxicity tests by means of MTT and cell differentiation by means of qPCR. RESULTS: The data showed that mesenchymal stromal cells from bone marrow treated for up to 21 days in the presence of bovine tendon extract diluted at diminishing concentrations (1:10, 1:50 and 1:250) promoted activation of biglycan, collagen type I and fibromodulin expression. CONCLUSION: Our results show that bovine tendon extract is capable of promoting differentiation of bone marrow stromal cells in tenocytes.